SITU CIBEUREUM AS OASIS: CYCLING COMMUNITY HUB AND RECREATIONAL PARK IN SITU CIBEUREUM, BEKASI - Inggita Saffanah, Cynantya
Amid the density of Bekasi Regency as one of the largest industrial areas in Indonesia, people need their own space for recreation, express themselves, and take a break from the tiring city life. One of the spaces chosen by the people of Bekasi Regency for this activity is Situ Cibeureum. Situ Cibeureum is located in the middle of the city and has natural environmental assets in the form of a lake which is a destination for the surrounding community for afternoon runs, culinary tours, and meeting fellow bicycle community activists in the area. The project seeks to facilitate existing activities and develop the function of the area according to land use to become an educational recreation park and bicycle community center in Bekasi Regency. The fictitious project of an Educational Recreation Park and Bicycle Community Center in Bekasi Regency aims to design educational natural recreation, facilitate hobbies and the bicycle community of the surrounding community who choose Situ Cibeureum as their travel destination, and provide an interesting natural space experience among the densely packed Bekasi Regency as their destination. This goal responds to several phenomena that occur at the site, including the Bekasi Regency aggressively encouraging the trade and tourism sector, the need for efforts to protect the environment and hydrological functions around it, inadequate recreational facilities on the site, and the increasing trend of bicycle use in Bekasi as a lifestyle. Therefore, the design process applies several foundations that become the standard design criteria, including the creation of a community space that attracts users to interact with each other, the creation of an attractive space, and providing a separate space experience for each user. The design criteria were formed to try to answer each approach comprehensively and provide the atmosphere, activities, and concepts of the existing space. Activities for cyclists that will be accommodated in this project include chatting with fellow bicycle community friends, improving and sharing knowledge about bicycles and their supporting equipment, providing space to learn cycling for children, and providing special spaces for BMX and MTB cyclists to do activities according to their needs, and down the river to cycle. In addition, water tourism activities that are accommodated in this project include walking around the deck, culinary tours, and buying souvenirs. All of these activities are integrated into the site based on the theory of sense of community, sociopetal space, and sense of place.